2011
DOI: 10.1590/s1413-70542011000100011
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagação de Dioscorea multiflora Grised

Abstract: Dioscorea multiflora uma planta nativa do Sul do Brasil produz a diosgenina como metabólito secundário majoritário, uma substância potencialmente usada pela indústria farmacêutica para a produção de cortisona e substâncias com ação contraceptiva. Objetivou-se, neste trabalho otimizar o protocolo de micropropagação de D. multiflora, visando a produção de mudas em escala comercial. Segmentos nodais subcultivados em meio MS sólido foram transferidos para multiplicação em meio MS suplementado com BAP (0,01; 0,1; 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
6
0
3
Order By: Relevance
“…Comparable to our study, in many species from various botanical families, e.g., Drosera intermedia (Rejthar et al, 2014), or Thermopsis turcica (Tekdal and Cetiner, 2014), in vitro propagation using zeatin led to improvements of previously published protocols, based on the application of other cytokinins (Cenkci et al, 2009;Grevenstuk et al, 2010). On the other hand, for numerous species from the Dioscoreaceae family, BA still remains sufficiently effective for in vitro propagation, e.g., for T. chantrieri (Charoensub et al, 2008), Dioscorea multiflora (de Souza et al, 2011), D. zingiberensis (Chen et al, 2003), and. D. fordii (Yan et al, 2011).…”
Section: Effect Of Cytokinins On Shoot Organogenesismentioning
confidence: 99%
“…Comparable to our study, in many species from various botanical families, e.g., Drosera intermedia (Rejthar et al, 2014), or Thermopsis turcica (Tekdal and Cetiner, 2014), in vitro propagation using zeatin led to improvements of previously published protocols, based on the application of other cytokinins (Cenkci et al, 2009;Grevenstuk et al, 2010). On the other hand, for numerous species from the Dioscoreaceae family, BA still remains sufficiently effective for in vitro propagation, e.g., for T. chantrieri (Charoensub et al, 2008), Dioscorea multiflora (de Souza et al, 2011), D. zingiberensis (Chen et al, 2003), and. D. fordii (Yan et al, 2011).…”
Section: Effect Of Cytokinins On Shoot Organogenesismentioning
confidence: 99%
“…Diferentemente deste trabalho com a umburana, a maior parte das pesquisas para o estabelecimento de protocolos de micropropagação, têm sido realizada utilizando-se o segmento nodal para a multiplicação (SOUZA et al, 2004;SANTANA et al, 2011;SOUZA et al, 2011). SOUZA et al (2011), comentam que dentre os tipos de explantes mais utilizados, as gemas apicais e axilares e os segmentos nodais, promovem clones true-to-type, ou seja, idênticos à planta matriz e por isso são os mais indicados para a multiplicação e conservação in vitro de genótipos elites.…”
Section: Resultsunclassified
“…Several studies have demonstrated the importance of using sucrose in the culture medium for in vitro cultivation of different species. In the micropropagation multiplication stage of Dioscorea multiflora in testing different concentrations of BAP and sucrose, Souza et al (2011) observed that the medium supplemented with 20 g L -1 of sucrose and 0.1 mg L -1 BAP resulted in a greater number of shoots and longer shoots for the species. In studying procedures for in vitro establishment of three species of the genus Ocotea, Moritz et al (2009) found that the plants presented slow but healthy development with 30 g L -1 of sucrose, while the use of higher concentrations (90 and 120 g L -1 ) negatively influenced plant development.…”
Section: Discussionmentioning
confidence: 99%
“…Currently applications of micropropagation of native species are mainly destined to: genotypes considered to be difficult to multiply by traditional propagation methods (PINHAL et al, 2011); those which produce secondary metabolites of pharmacological interest (SOUZA et al, 2011); to the in vitro germplasm conservation of endangered species (CAMPOS et al, 2013); and to the development of molecular biology techniques.…”
Section: Introductionmentioning
confidence: 99%